Infants born to women with substance use: Exploring early neurobehavior with the Dubowitz neurological examination - H. Tuhkanen; M. Pajulo; H. Jussila; E. Ekholm (Elsevier Ireland Ltd., 2025)
Background
There is a special concern regarding substance using pregnant women due to the possible adverse effects on the infant. While the immediate effects of prenatal substance exposure are well known, the long-term data on the infants' neurodevelopment is inconclusive.
Aims
The purpose of this study was to assess early neurobehavior of infants of mothers with substance use using the Dubowitz examination and to follow their neuromotor development until one year of age.
Study design and subjects
Ninety-five pregnant women with a recent history of substance use were recruited and followed up at the maternity outpatient clinic. Follow-up data was collected from hospital records and maternal interviews. The Dubowitz neurological examination was performed to the 54 clinically healthy term infants. The results were converted into optimality scores and compared to normative values from clinically healthy term infants derived from a separate normative population. The infant's neuromotor development was followed up to one year of age.
Results
Only 7% of the infants born to women with recent or current substance use reached optimal scores (<30.5) in the Dubowitz neurological examination compared to 95% reported in normative population. Sixty-three percent of the newborns needed follow-up based on physiotherapeutic assessment of neurobehavior. By 12 months of age, the neuromotor status of 88% (n = 30) of these infants was found normal.
Conclusions
A high percentage of infants of mothers who were referred prenatally to hospital due to substance use showed suboptimal neurological findings during their first days of life.